Hybrid WENO Schemes with Lax-Wendroff Type Time Discretization (Journal of Mathematical Study, 2017)
In this paper, we investigate the performance of a class of the hybrid weightedessentially non-oscillatory (WENO) schemes with Lax-Wendroff time discretizationprocedure using different indicators for hyperbolic conservation laws. The main ideaof the scheme is to use some efficient and reliable indicators to identify discontinuityof solution, then reconstruct numerical flux by WENO approximation in discontinuousregions and up-wind linear approximation in smooth regions, hence reducingcomputational cost but still maintaining non-oscillatory properties for problems withstrong shocks. Numerical results show that the efficiency and robustness of the hybridWENO-LW schemes.